Functional and radiological outcomes of intertrochanteric fractures treated with proximal femoral nail - Chopra, Mayur; Srivastava, Sanjay Kumar; Kumar, Sumit; Mishra, Deepak Kumar (International Journal of Research in Orthopaedics, 2020)
Background: Hip fracture is one of the most invalidating diseases affecting geriatric populations and in fall related fractures, they lead to most severe morbidity and mortality. Their surgical treatment allows stable fracture fixation which allows the early weight bearing. Many devices have been developed, yet mechanical failures still occur. The aim of this study was to assess the functional and radiological outcomes of intertrochanteric fractures treated with proximal femoral nail. Methods: 46 patients with intertrochanteric fractures fixed with proximal femoral nail were assessed. Functional outcome was measured by Harris hip score (HHS) and lower extremity functional scale (LEFS) and radiological outcome was measured by tip apex distance (TAD), any changes in neck shaft angle, neck length and the offset as compared to uninjured hip. Results: The tip apex distance on the postoperative X-ray was found to be 22.02±2.499 mm, change in the neck length as compared to the uninjured hip was found to be 1.507±1.1808 and change in the offset and neck shaft angle was 1.470±1.0126 and -1.602±1.5992 respectively. The LEFS was found to be 70.63±6.584 whereas the HHS was found to be 90.35±7.593 Conclusions: With the increase in TAD the functional and radiological outcome worsens. It was also seen that the cutoff of 25 mm stands true in predicting the outcome of the patients with PFN in intertrochanteric fractures. Hence, the TAD should be routinely measured and if found more than 25 mm then proper precautions like delayed weight bearing may be advised.